An Analysis of the Legal Effectiveness of Compensation Mechanisms for Communities and Persons Affected by the Oil and Gas Projects in Uganda: A Case Study of the Albertine Region - Rebecca Nabo (Uganda Christian University, 2025)
The aim of this paper was to analyse the effectiveness of the law of compensation to persons affected in the oil and gas sector in Uganda a case study in the Albertine Region. The land that is rich in the minerals shall be owned by the government of Uganda as per Article 244 of the Constitution of Uganda. This places a duty on the government to effectively compensate the affected people and should be done with authenticity and diligence. The study aimed at analysing the legal framework governing compensation practices and evaluated the impact on affected communities. It sought to identify challenges and opportunities for improvement, ensuring that compensation processes are authentic, diligent and priotise the rights and interests of affected individuals. The research investigated the extent to which current laws and policies protect the rights of compensation, livelihood restoration and cultural preservation. It also explored the experiences and perspectives of communities affected by oil and gas projects, highlighting successes and challenges in the compensation process. By examining the effectiveness of compensation laws on the Albertine Region, this study aimed to contribute to the development of more equitable and sustainable practices in Uganda’s oil and gas sector. The findings and recommendations informed policy practice, ensuring that the rights and the interests of affected communities are respected and protected. Ultimately, this research sought to promote more responsible and inclusive development in Uganda’s oil and gas sector, balancing economic growth with social justice and environmental sustainability. By priotising the needs and rights of affected communities, the government and industry stakeholders should work towards more equitable outcomes that benefit both the country and its people.
Undergraduate